The Effectiveness of Cognitive Behaviour Therapy on Relapse in Schizophrenia Patients with Hallucinations - Uswatun Khasanah; Yossie Susanti Eka Putri; Mustikasari Mustikasari (Poltekkes Kemenkes Surakarta, 2026)
Background: Schizophrenia is a chronic mental disorder characterized by psychotic symptoms such as hallucinations and delusions. Relapses in schizophrenia patients often occur even after undergoing pharmacological treatment. Cognitive Behaviour Therapy (CBT) has been reported to be effective in reducing relapses through cognitive restructuring and improving patients' coping with psychotic symptoms. This systematic review aims to assess the effectiveness of CBT on reducing relapse rates in patients with schizophrenia, especially in hallucination. Methods: The systematic review was conducted using the JBI approach. The included articles were primary studies with an RCT or quasi-experimental design, published between 2015 and 2024, and available in full text. The selection process was conducted using the PRISMA method, and the final results consisted of 7 articles that met the inclusion criteria. Results: Most studies show that CBT is effective in reducing relapse, improving quality of life or social functioning, and reducing positive and negative psychotic symptoms. Culturally-based CBT and CBT by videoconference have been reported to expand access to intervention. The side effects of CBT are relatively low, but some studies report a decline in impact after therapy is discontinued. Conclusion: CBT is effective in preventing relapse in schizophrenia patients with hallucinations by reducing psychotic symptoms and improving patient coping. Further research is needed to evaluate the long-term effectiveness of CBT.